Lactobacillus role during conditioning of refrigerated and vacuum-packaged Argentinean meat - Fadda, Silvina G. (2008)
The role of Lactobacillus strains with bioprotective and technological potential on raw beef during 15 days of storage under vacuum at 7 °C was investigated. The assayed strains were able to grow on the meat, Lactobacillus curvatus CRL705 and Lactobacillus sakei 23K showing the highest competitiveness. A net increase of amino acids was determined in inoculated samples when compared to the control, this being maximal for Lactobacillus plantarum CRL681. Although an important endogenous activity of meat sarcoplasmic proteins was observed, the disappearance of protein bands and the generation of a new one were detected as a consequence of Lactobacillus growth. A synergistic effect of Lactobacillus in combination with the muscle proteolytic enzyme complex can be suggested. From the studied strains, the bacteriocin producer L. curvatus CRL705 may be considered as a good candidate to contribute to meat ageing by means of small peptides and free amino acids generation while improving shelf life.